2019
DOI: 10.18203/2394-6040.ijcmph20193640
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of utilization of postnatal care services in urban area Jabalpur district

Abstract: Background: Postnatal period is a vulnerable time, because most maternal and new born deaths occur during this period, especially immediately after childbirth. Postnatal care in the first hours and days after childbirth could prevent the great majority of these deaths. The objective of study was to assess the utilization of post-natal care and associated factors for low utilization in urban area of Jabalpur district.Methods: A community based cross-sectional study was carried 360 mothers who delivered in last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Pandey D et al . [ 8 ] in their study observed that, no significant association was found with variables like age of mother, order of delivery and occupation of husband as similar study also done by Sharma et al . and Ranganath et al .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Pandey D et al . [ 8 ] in their study observed that, no significant association was found with variables like age of mother, order of delivery and occupation of husband as similar study also done by Sharma et al . and Ranganath et al .…”
Section: Discussionsupporting
confidence: 51%
“…[ 7 ] Utilization of postnatal care can be affected by large number of factors including socio-demographic factors, economic factors, accessibility and availability of maternal and child health services etc. [ 8 ] Understanding the factors that influence care-seeking behaviour for postpartum services in India is vital to improve quality of care and planning appropriate interventions. Knowing the activities developed and results achieved by postnatal care programs is important for the planning and improvement of Primary health care.…”
Section: Introductionmentioning
confidence: 99%
“…19 Previous study reported the need for PNC utilization and awareness were significantly related to the education of the mother. 16,20,21,22,23 Some studies also showed increase in post-natal visits occurs significantly with increase in socioeconomic status. 16,23,24,25 In our study as most of them were educated as 86.93% were having higher secondary education and above it and not from low socioeconomic status.…”
Section: Routinementioning
confidence: 99%
“…16,20,21,22,23 Some studies also showed increase in post-natal visits occurs significantly with increase in socioeconomic status. 16,23,24,25 In our study as most of them were educated as 86.93% were having higher secondary education and above it and not from low socioeconomic status. So poor counselling for postnatal care both for the mother and babies remained the main cause than education and socioeconomic status.…”
Section: Routinementioning
confidence: 99%
“…The rst postnatal visit should happen as soon as after delivery-ideally within 24 hours-if the birth takes place at home. It is advised to make three more PNC contacts on day three, between days 7-14 after delivery, and six weeks after delivery [14].…”
Section: Introductionmentioning
confidence: 99%